Chapter Gurgaon: Unfinished City, a photographic essay - Khare, Sarth (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
As Gurgaon expands horizontally and vertically, it continues to transition from farms to urban villages to a concrete maze. This photographic project documents the growth of Gurgaon a city recently developed near India's capital, Delhi. It is a booming financial and industrial center, home to most Multinational Corporations (MNCs) and has third highest per-capita income in India. As its advocates often like to point out, Delhi's booming neighbor has 1,100 high-rises, at least 30 malls and thousands of small and big industries. On the other hand, as its detractors unfailingly like to note, the dust bowl's population has grown two and a half fold, it has 12-hour power blackouts, and its groundwater would probably not last beyond this decade. Gurgaon's transformation began sometime around 1996, with the advent of Genpact, then a business unit of General Electric. Other multinational companies followed it slowly thereafter. It helped that the city was a few kilometers away from Delhi. Two decades on, Gurgaon is already "on its deathbed." From 0.8 million in 2001, the city is expected to reach a population of 6.9 million in 2031. It is speckled with glass buildings with curtain walls, and swish apartment blocks with Greco-Roman influences, but there is little water or power for them. These numbers alone don't capture the lived reality of Gurgaon, though. The skyline that its older residents were accustomed to has completely disappeared. And yet on the periphery, one sees the "Unfinished City" growing. The landscapes and flora shouting; their sentiments brutalized by evictions and concrete. Slaughtered farms now seem witness to monstrosity with desolate faces and fading memories. Set in 2014 the project explores the ephemerality of Gurgaon's glamor and defective town planning. Families had been displaced, laborers' children were growing up on heaps of cement, and farmlands had turned into things of memories.